Lacticaseibacillus rhamnosus Fermentation Ameliorates Physicochemical Properties, Physiological Activity, and Volatile and Non-Volatile Compounds of Mango Juice: Preliminary Results at Laboratory Scale - Jinlin Fan; Weiling Guo; Zheng Xiao; Jiacong Deng; Feifei Shi (Foods)
Lacticaseibacillus rhamnosus is a strain predominantly used for juice production because of its excellent fermentation characteristics and strong acid production capacity. However, the influence of L. rhamnosus on the quality of mango juice has not yet been determined. Therefore, the effects of L. rhamnosus FJG1530 on the physicochemical properties, physiological activity, and volatile and non-volatile compounds of mango juice were extensively examined in this study. The data showed that L. rhamnosus FJG1530 possessed strong adaptability to mango juice, reducing its total sugar and increasing its total flavonoids. L. rhamnosus FJG1530 fermentation enhanced the ability of mango juice to clear the free radicals ABTS and DPPH, as well as improving the inhibition of lipase and α-glucosidase. In addition, L. rhamnosus FJG1530 treatment improved the volatile compounds in mango juice, especially promoting the formation of acids and alcohols. Simultaneously, metabolomic analysis revealed that 592 non-volatile compounds in mango juice were significantly changed by L. rhamnosus FJG1530 fermentation, with 413 dramatically increased and 179 significantly decreased metabolites. This study demonstrates that the fermentation process using L. rhamnosus FJG1530 was beneficial for ameliorating the quality of mango juice.